1999
DOI: 10.1152/jn.1999.82.1.501
|View full text |Cite
|
Sign up to set email alerts
|

Motor Unit Substitution in Long-Duration Contractions of the Human Trapezius Muscle

Abstract: We examined the activity pattern of low-threshold motor units in the human trapezius muscle during contractions of 10 min duration. Three procedures were applied in sequence: 1) static contraction controlled by maintaining a constant low level of the surface electromyogram (EMG)-detected root-mean-square signal, 2) a manipulation task with mental concentration, and 3) copying a text on a word processor. A quadrifilar fine-wire electrode was used to record single motor unit activity. Simultaneously, surface ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
122
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 13 publications
8
122
0
1
Order By: Relevance
“…A number of studies have reported activation rotation to compensate for fatigue at the muscular level during prolonged muscle activities at sub-maximal intensity, but none has done this at the maximal intensity level. For example, during the later portion of a 10-min sustained contraction of elevating the shoulder at about 5% maximal level, Westgaard and de Luca (1999) observed that low-threshold motor units of human trapezius muscle showed periods of inactivity and were substituted by motor units of higher recruitment threshold. This phenomenon was not noticed during the first few minutes of the contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported activation rotation to compensate for fatigue at the muscular level during prolonged muscle activities at sub-maximal intensity, but none has done this at the maximal intensity level. For example, during the later portion of a 10-min sustained contraction of elevating the shoulder at about 5% maximal level, Westgaard and de Luca (1999) observed that low-threshold motor units of human trapezius muscle showed periods of inactivity and were substituted by motor units of higher recruitment threshold. This phenomenon was not noticed during the first few minutes of the contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The silenced motor units were reactivated after a period of "rest." The authors speculated that the motor unit "substitution" protects motor units from excessive fatigue (Westgaard and de Luca, 1999). Another study (Sogaard, 1995) involved recording single motor units from elbow flexors during static and dynamic elbow flexion contractions of human participants at about 10% maximal intensity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms behind this relationship may be an association between EMG gaps and the rotation of motor unit recruitment (24), which thus possibly prevents the overload of muscle fibers. In our study, very few EMG gaps were found, and both input devices may increase the risk of symptoms in the forearm, the computer mouse possibly causing the largest effect.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged low-level activity of muscle has been implicated to lead to muscle pain in other muscle groups due to the continuous and relatively high activity of a fraction of the motor units in the muscle (Ha È gg 1991, Westgaard andDeLuca 1999). In addition, contraction levels of the trunk extensors of as low as 2% of maximum voluntary force have been shown to impair oxygenation of this musculature (McGill et al 2000).…”
Section: Introductionmentioning
confidence: 99%